Consulting report – Natura Cosméticos SA - Capcha Rivera, Cinthia Enedina; Kang Cabrera, Hoseok Antonio (Pontificia Universidad Católica del Perú, 2017)
Natura S.A is a Brazilian company that sells beauty products and personal care through direct sales. Currently it has a greater presence in the Latin American market: Brazil, Argentina, Mexico, Peru Colombia and Chile. On the other hand, Atento is a Peruvian company that provides the services of the contact center for all operations of Natura Latin America, without including Brazil. The main problem identified is the inefficient management of the contact center by Natura which is deteriorating the quality of the service. The inefficiencies are related to the lack of quality tools, limited definition of indicators, poor staff management, and poor added value during the call service. In this sense, the Regional Customer service area (Natura) is interested in look for better processes and indicators for the management of the contact center in order to find a model that optimizes the control of the performance of the supplier. The literature reviewed to develop the solution is about quality management systems, contact center outsourcing models, methods to add value to services, and process improvement methodologies. After that, three alternatives were developed where each of one was evaluated according factor of costs, innovation, risk, value added, feasibility and feedback of Natura. The final proposal has two phases, the first one is to implement Business Intelligence in which it will be possible to analyze the database of the calls in order to develop initiatives of improvement in short and long term, as the reduction of unwanted calls. After that, in order to complement the business intelligence proposal, the second phase will be the implementation of the value-added strategy in which it will look for higher quality and personalization of call service according to the profile of the consultants per country. The implementation plan implies an active participation of both parties. Finally, the investment to implement this proposal is 68,300 PEN and the expected benefits are reduction of expenses of 750,000 PEN, process optimization and improvement of consultant’s satisfaction.

Natura S.A es una empresa brasilera comercializadora de productos de belleza y cuidado personal mediante la venta directa. Actualmente tiene mayor presencia en el mercado latinoamericano: Brasil, Argentina, Mexico, Peru Colombia y Chile. Por otro lado, Atento es una empresa peruana que brinda los servicios del centro de contacto para todas las operaciones de Natura Latinoamérica sin incluir Brasil. El principal problema identificado es la ineficiente gestión interna del centro de contacto por parte de Natura que está deteriorando la calidad del servicio. Las ineficiencias están relacionadas a la falta de herramientas de control, limitada definición de indicadores, deficiente gestión de personal, y poco valor agregado durante la atención de llamadas. En este sentido, el área de Atención Regional (Natura) está interesado en la búsqueda de mejores procesos e indicadores para la gestión del centro de contacto y encontrar un modelo que optimice el control del desempeño del proveedor. La teoría investigada para desarrollar la solución al problema son sistemas de gestión de calidad, modelos de tercerización de centros de contacto, métodos para agregar valor a los servicios, y metodologías de mejora de procesos. Luego se desarrolló tres alternativas, las cuales fueron evaluadas de acuerdo a factores de costos, innovación, riesgos, valor agregado, factibilidad y valoración de Natura. La propuesta final comprende de dos fases, la primera es la implementación de inteligencia de negocios (Business Intelligence) en el cual se podrá analizar la información de las llamadas para desarrollar iniciativas de mejora a corto y largo plazo, como la reducción de llamadas no deseadas. Mientras que la segunda fase se basa en la estrategia de valor agregado, el cual se buscara mayor calidad y personalización en la atención de llamadas de acuerdo al perfil de las consultoras. Finalmente, la inversión requerida anual es de S/. 68,000 y los beneficios esperados son la reducción de gastos en S/.750,000 soles, optimización de procesos y mejora de satisfacción de consultoras.
Keywords: Calidad total; Servicios al cliente; Empresas -- Gestión; Control de procesos; https://purl.org/pe-repo/ocde/ford#5.02.04